Alternative Splicing Dynamics of the Hypothalamus–Pituitary–Ovary Axis During Pubertal Transition in Gilts - Pan, Xiangchun; Li, Qingnan; Chen, Danxia; Gong, Wentao; Li, Nian; Jiang, Yao; Zhang, Hao; Chen, Yaosheng; Yuan, Xiaolong (Frontiers in Genetics, 2021)
The timing of puberty in mammals marks the point at which reproduction becomes possible. Abnormalities that occur during puberty may exert negative effects on subsequent health outcomes. Alternative splicing (AS) has emerged as a significant factor in the transcription of genes and has also been reported to play a role in the timing of puberty. However, to date, the changes and dynamics of AS during the onset of puberty is extremely seldom explored. In the present study, we used gilts as a research model and investigated the dynamics of AS and differentially expressed alternative splicing (DEAS) events within the hypothalamus-pituitary-ovary (HPO) axis across pre-, in-, and post-puberty. We detected 3390, 6098, and 9085 DEAS events in the hypothalamus, pituitary and ovary, when compared across pre-, in- and post-pubertal stages, respectively. Within the entire HPO axis, we identified 22889, 22857, and 21055 DEAS events in the pre-, in-, and post-pubertal stages, respectively. Analysis revealed that the differentially spliced genes (DSGs) associated with staged DEAS events were likely to be enriched in the oxytocin signaling pathway, thyroid hormone signaling pathway, GnRH signaling pathway and oocyte meiosis. The DSGs associated with DEAS events across the entire HPO axis were enriched in endocytosis, the MAPK signaling pathway and the Rap1 signaling pathway. Then the AS of TAC1, TACR3, CYP19A1, ESR1, ESRRA and FSHR were likely to regulate the functions of the certain HPO tissues during the onset of puberty. These findings enhance our knowledge of how puberty is regulated by AS and shed new light on the molecular mechanisms underlying the timing of puberty in mammals.